2022
DOI: 10.1039/d2ra00530a
|View full text |Cite
|
Sign up to set email alerts
|

Unusual semiconductor–metal–semiconductor transitions in magnetite Fe3O4 nanoparticles

Abstract: Herein, we report the existence of a novel semiconductor–metal–semiconductor type transition in Fe3O4 nanoparticles by employing impedance spectroscopy techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…The activation energies ( E a ) were calculated from the slopes of the linear regions of plots between ln σ and 1000/ T of all prepared samples in different regions using the Arrhenius law given below:where σ o is the pre-exponential factor, E a is the activation energy, k B is the Boltzmann constant and T is the absolute temperature. 48 Table 2 shows the calculated values of E a ′s for the prepared samples in different regions at a representative frequencies of 1 kHz, 10 kHz and 100 kHz. We found that the BaTiO 3 sample has a large values of E a due to bigger grain size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation energies ( E a ) were calculated from the slopes of the linear regions of plots between ln σ and 1000/ T of all prepared samples in different regions using the Arrhenius law given below:where σ o is the pre-exponential factor, E a is the activation energy, k B is the Boltzmann constant and T is the absolute temperature. 48 Table 2 shows the calculated values of E a ′s for the prepared samples in different regions at a representative frequencies of 1 kHz, 10 kHz and 100 kHz. We found that the BaTiO 3 sample has a large values of E a due to bigger grain size.…”
Section: Resultsmentioning
confidence: 99%
“…where s o is the pre-exponential factor, E a is the activation energy, k B is the Boltzmann constant and T is the absolute temperature. 48 Table 2 shows the calculated values of E a ′ s for the prepared samples in different regions at a representative frequencies of 1 kHz, 10 kHz and 100 kHz. We found that the BaTiO 3 sample has a large values of E a due to bigger grain size.…”
Section: Ac Conductivitymentioning
confidence: 99%
“…As such, ternary metal composites are a reasonable system, as Pt and Ru loadings can be effectively varied. There are several reports on ternary metal composites for the MOR; however, the onset potential for the MOR of these catalysts is still higher than 0.6 V RHE due to the absence of Ru or the heterogeneous distribution of Ru. , Moreover, when transition metals are employed in acids, one unavoidable problem is that the catalyst will gradually transform under acidic conditions through processes such as rearrangement and partial dissolution. Thus, finding a suitable substrate, regulating the loading of Pt, and investigating the change of catalyst under acidic conditions are of significance for the rational design of MOR catalysts.…”
Section: Introductionmentioning
confidence: 99%